Environmental parameters and analysis of crowd flow in an academic building of a university. Issue 1 (January 2021) - Lei, Wenjun; Tai, Chuanmin; Rong, Chuanliang; Qi, Xinye; Zhang, Linhua; Cong, Junzi
Academic buildings are the main gathering places in universities and colleges. The crowd flow could cause a change in environmental parameters of buildings. In other words, the change in environmental parameters in buildings can be somewhat reflective of the crowd flow. Therefore, field measurements of the crowd flow and environmental parameters in an academic building at a university were conducted in this study. During the periods of 7:30–8:00 and 13:20–13:50, the average speed of the crowd was the highest, which was about 1.2 m/s; the CO2 concentration was low, which was about 750 ppm. In the periods of 9:20–9:50 and 15:10–15:40, the average speed of people walking in the opposite directions was the lowest, which is 0.42 m/s; however, the CO2 concentration could reach 1800 ppm. Test results showed that the variations of CO2 concentrations were inversely related to the average speed of the crowd in the evacuation passage, except for the periods of 7:30–8:00 and 13:20–13:50. Spatial separation and physical separation could be used in the management of personnel flow in the academic building. The results may provide reference for the management of the crowd flow in similar academic buildings of other universities.